Reusable learning objects in a distributed content management system for a project-based pedagogy. (1st June 2005) - Faro, Alberto; Giordano, Daniela; Mineo, Simona
This paper illustrates how to apply the reusable learning objects approach, together with ontologies and the intelligent agents technology, in the context of a project-based pedagogy to provide the learners of a design course with design cases that are shared across different design communities through a distributed content management system.